Justification of the need to take into account the individual characteristics of synchronized swimmers when compiling a solo program - Aikin, V. A.; Kuksina, A. A.; Korichko, A. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the need to take into account the constitutional characteristics of female ath-letes when compiling solo programs in synchronized swimming.Methods and structure of the study. The analysis of arbitrary solo programs of athletes from different countries in the finals of the World Championships in Gwangju, the Republic of Korea, representatives of the countries of Russia, Spain and Japan was carried out in order to identify the constitutional features of athletes when compiling solo programs in synchro-nized swimming.Results and conclusions. A visual analysis of the competitive activity and individual characteristics of synchronized swim-mers from different countries revealed that in the process of compiling a solo program, the constitutional and individual characteristics of synchronized swimmers are taken into account in order to create effective compositions. Athletes whose programs are distinguished by a modern and high level have similar constitutional characteristics, which include: asthenic or normosthenic body type, long limbs, height, within 165-175 cm, good joint mobility and plasticity of the feet, wide shoul-der girdle. These sportswomen have well-developed special endurance, speed-strength qualities and coordination abilities.